Development and steroidogenic properties of the Bidder's organ of the tadpole of Rhinella arenarum (Amphibia, Anura) - Sassone, Alina Grisel (2015)
Several studies suggested that in anuran amphibians steroidogenic enzymes are critical for gonadal differentiation, proposing that the amount of sex steroids would adjust this differentiation. Among anurans, bufonids are important for the study of sex differentiation due to the presence of Bidder's organ (BO) that differentiates as a rudimentary ovary in the cephalic portion of the genital ridge. Considering that in adult males of Rhinella arenarum, the BO synthesizes estradiol, the main purpose of this work is to examine, in this species, the morphogenesis of BO and the steroidogenic capacity of this organ during larval development. BO and the proper gonads are distinguished from Gosner stage 26. During metamorphosis, BO primary oogonia develop in oogonia in nests, early previtellogenic oocytes and late previtellogenic oocytes in follicles while proper gonads remain undifferentiated. Aromatase was detected by immunohistochemistry in almost all the largest follicles of the BOs while the cytochrome P450 side-chain cleavage was observed in only few oocytes. The proper gonad was not immunoreactive in any stage. The determination of aromatase and 5α-reductase activities showed that the population of tadpoles between stages 36-41 is not homogeneous in terms of aromatase activity. In addition, from stage 26 to the end of metamorphosis, all the stages were able to produce estradiol from endogenous substrate but stages 40-41, corresponding to the end of pro-metamorphosis, produced the highest values. In conclusion, BO is able to synthesize estradiol from endogenous precursors and proper gonad remains undifferentiated at least until the end of the metamorphosis.